2023
DOI: 10.3390/ijms24032126
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Radix Astragali and Safflower Promotes Angiogenesis in Rats with Ischemic Stroke via Silencing PTGS2

Abstract: Promotion of angiogenesis and restoration of the blood flow in the ischemic penumbra is an effective treatment for patients with ischemic stroke (IS). Radix astragali-safflower (AS), a classic herbal pair for accelerating blood circulation and dispersing blood stasis, has been used for thousands of years to treat patients with IS in China. Even so, the mechanism of the treatment of IS by AS is still undecipherable. In the current study, network pharmacology was firstly employed to unveil the mechanism of AS in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
6
0
2
Order By: Relevance
“…Additionally, it was found that high dose of safranal (40 mg/kg) can significantly attenuate these symptoms, which was in line with the data from Sadeghnia et al ( 27 ) indicating that safranal has protective effects on MCAO/R rats. A previous study indicated that angiogenesis is conducive to the recovery of blood supply in ischemic penumbra, thus promoting the activation of neurons ( 46 ). Angiogenesis is a process that enhances the proliferative and migrative potentials of vascular endothelial cells and the reconstruction of new vascular networks ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it was found that high dose of safranal (40 mg/kg) can significantly attenuate these symptoms, which was in line with the data from Sadeghnia et al ( 27 ) indicating that safranal has protective effects on MCAO/R rats. A previous study indicated that angiogenesis is conducive to the recovery of blood supply in ischemic penumbra, thus promoting the activation of neurons ( 46 ). Angiogenesis is a process that enhances the proliferative and migrative potentials of vascular endothelial cells and the reconstruction of new vascular networks ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is considered as the most indispensable cytokine to promote angiogenesis ( 43 ). TGF-β1 and bFGF-2 are both pro-angiogenesis and are involved in the migration and proliferation of endothelial cells ( 46 ). PDGF combined with its receptor are responsible for recruiting brain pericytes into newly formed vessels during the progression of angiogenesis ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Astragali Radix ‐ Carthami Flos is a classic herbal pair that appears in many formulas such as the buyang huanwu decoction. Modern pharmacological studies have found that Astragali Radix ‐ Carthami Flos reduces the volume of cerebral infarcts and neuronal damage, and also promotes angiogenesis in MCAO/R rats by modulating the balance between anti‐angiogenic factors (PF4, TSP1) and pro‐angiogenic factors (bFGF, TGF‐β) (Xu et al, 2023). The effect of Astragali Radix ‐ Carthami Flos on activating blood and resolving stasis was significantly better than that of Astragali Radix and Carthami Flos alone, and the best effect was found when Astragali Radix ‐ Carthami Flos was used in a 5:1 ratio to intervene in ischemia–reperfusion injury in rats (Yi et al, 2022).…”
Section: The Synergistic Role Of Compatibility In Tcm Formulas In The...mentioning
confidence: 99%
“…In recent years, it has been mentioned in many studies that the treatment of traditional Chinese medicine can improve blood ow, promote neovascularization, accelerate damage repair and achieve good curative effect [13][14][15][16] . We believe that using the minimally invasive concept combined with traditional incision and drainage may achieve satisfactory e cacy.…”
Section: Discussmentioning
confidence: 99%